Analisis Manajemen Penyimpanan Sediaan Vaksin COVID-19 di Instalasi Farmasi RSUD S. K. Lerik Kota Kupang - Sarifudin, Barbara Azalya; Lette, Arman Rifat; Kulla, Selviana Take (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
The COVID-19 pandemic poses a vast morbidity and mortality burden and disrupts communities and economies globally, including Indonesia. Vaccination is an essential prevention. Vaccine storage must be maintained to preserve its potency and safety. This study determined the suitability of the storage and COVID-19 vaccine preparations at the Pharmacy Installation of RSUD S. K. Lerik Kupang City, based on the 2020 Good Drug Distribution Method (Cara Distribusi Obat yang Baik or CDOB) standard and the 2021 Ministry of Health regarding Technical Instructions for Vaccination Implementation in Combating the Corona Virus Disease 2019 (COVID-19) Pandemic. This study used a qualitative, non-experimental observational method, data collection, structured interviews, and documentation. The storage management assessment for the COVID-19 vaccine is carried out using Zuhroh's checklist tool. The results show that the COVID-19 vaccine storage system at the RSUD S. K. Lerik needs development to follow CDOB 2020 and Kepmenkes 2021 rules fully. Indicators results that are below the standard: training and evaluation, the unavailability of a hygiene schedule, air ventilation, Vaccine Vial Monitor (VVM) images, expiration places, quarantine places, destruction of damaged vaccines, weekly and monthly recording maintenance, and also unavailability of replacement equipment during the implementation, repair, maintenance, and calibration of equipment.